Quantitative Contribution of rs75017182 to Dihydropyrimidine Dehydrogenase mRNA Splicing and Enzyme Activity. Issue 4 (26th May 2017) - Nie, Q; Shrestha, S; Tapper, EE; Trogstad‐Isaacson, CS; Bouchonville, KJ; Lee, AM; Wu, R; Jerde, CR; Wang, Z; Kubica, PA; Offer, SM; Diasio, RB
Abstract : Dihydropyrimidine dehydrogenase (DPD; DPYD gene) variants have emerged as reliable predictors of adverse toxicity to the chemotherapy agent 5‐fluorouracil (5‐FU). The intronic DPYD variant rs75017182 has been recently suggested to promote alternative splicing of DPYD . However, both the extent of alternative splicing and the true contribution of rs75017182 to DPD function remain unclear. In the present study we quantified alternative splicing and DPD enzyme activity in rs75017182 carriers utilizing healthy volunteer specimens from the Mayo Clinic Biobank. Although the alternatively spliced transcript was uniquely detected in rs75017182 carriers, canonically spliced DPYD levels were only reduced by 30% ( P = 2.8 × 10 ‐6 ) relative to controls. Similarly, DPD enzyme function was reduced by 35% ( P = 0.025). Carriers of the well‐studied toxicity‐associated variant rs67376798 displayed similar reductions in DPD activity (31% reduction). The modest effects on splicing and function suggest that rs75017182 may have clinical utility as a predictor of 5‐FU toxicity similar to rs67376798.